Is a History of Gestational Diabetes Associated With Long‐Term Mental Health?—Findings From the GEMS 5‐Year Follow Up Study - Phyllis Ohene‐Agyei; Greg D. Gamble; Debbie Samuel; Oluwatoyin Oladimeji; Qiliang Liu; Jane E. Harding; Caroline A. Crowther (Brain and Behavior, 2025)
ABSTRACT Introduction Gestational diabetes mellitus (GDM) is associated with poor long‐term maternal metabolic health. However, there is limited evidence on the effect of GDM on later maternal mental health. We, therefore, aimed to compare mental health outcomes between women who had GDM and women who did not five years after the index pregnancy. Methods A follow‐up study of women diagnosed with GDM using the International Association of Diabetes in Pregnancy Study Group (IADPSG) criteria matched to a random sample of women not diagnosed with GDM for maternal age, ethnicity, and BMI. Participants completed questionnaires screening for anxiety (6‐item State‐Trait Anxiety Inventory), depression (Edinburgh Postnatal Depression Scale), or health‐related quality of life (SF‐36). Results Of the 563 participants, 233 (41.4%) were diagnosed with GDM in their index pregnancy. At follow‐up, 152/563 (27.0%) reported an increased risk of symptoms of poor mental health, and this was similar in women who were and were not diagnosed with GDM. There was no difference between the two groups for risk of anxiety, [aRR: 0.76 (0.50, 1.22)] or depression [aRR: 1.11 (0.74, 1.66)]. However, women diagnosed with GDM reported lower mean SF‐ 36 scores for general health [aMD: −3.91 (−7.14, −0.68)] and social functioning [aMD: −3.61 (−7.05, −0.16)] than women without GDM. Conclusion The risk of poor mental health is common five years after birth. However, GDM diagnosis was not associated with an increased risk for anxiety or depression, although GDM may affect women's perception of their later general health and social functioning.